Response of Dayak onion (Eleutherine bulbosa Merr.) plant growth after application of biosaka from the Asteraceae family - Siti Asriati; Elimasni Elimasni; Isnaini Nurwahyuni (Universitas Islam Negeri Sumatera Utara, 2025)
Public interest in the use of medicinal plants continues to grow. One of the medicinal plants that has been developed is dayak union (Eleutherine bulboba Merr.), which is believed to be able to cure various diseases. This research aims to determine the best growth response of Dayak onion after the application of biosaka from the Asteraceae family. The main implications of biosaka for agriculture are significant cost efficiency in production, improved plant and soil health, and the promotion of sustainable and environmentally friendly farming by improving land ecosystems. Biosaka is made by taking 60 g of each plant and then grinding it until it is dark brown and slightly foamy. Biosaka extraction produces approximately 20 ml. The experiment was conducted at the Faculty of Mathematics and Natural Sciences, University of North Sumatra from December to March 2025. The design used in this experiment is a Completely Randomized Design (CRD) consisting of 5 treatment levels of biosaka concentration, namely 0 ml/L, 3.5 ml/L, 4.5 ml/L, 5.5 ml/L, and 6.5 ml/L with eight replications. The data obtained were analyzed using SPSS version 22 software with ANOVA (Analysis of Variance) test. If the treatment has a significant effect, it is followed by DMRT (Duncan Multiple Range Test). The research results show that the application of a biosaka concentration of 6.5 ml/L yielded the highest results and had a significant effect on plant height, number of leaves, tuber diameter and number of shoots and tubers per clump.